Adoption of Livestock Insurance in Punjab: Extent and constraints - Singh, Simranjeet; Kaur, Arjinder; Arora, kashish (Indian Journal of Dairy Science, 2022)
The present study has been designed to investigate the extent of insurance coverage of dairy animals in Punjab and highlighting the constraints faced by the dairy households in its adoption. The primary data were collected from 100 dairy households in Patiala and Moga districts of Punjab based on their rank in milk production and secondary data were extracted from central and state government publications.Â The results of the study showed that Punjab ranked at 8th position among the states in terms of number of beneficiaries availing the dairy loan as well as the insurance with a total of 1877 beneficiaries in the state in the year 2018-19 and contributing to 4.8 per cent of the total number of beneficiaries in India. Out of the total number of animals in the sampled households which have adopted the insurance policy only 24.42 per cent of the animals were insured. The major constraint for non-adoption of insurance coverage was the small herd size of the livestock, while the main reason for discontinuing the policy and problem faced during the claim settlement was the low indemnity level provided by the insurance company. The major problem faced by the adopters of dairy insurance was the gap between the original market price and the sum insured. It was concluded that relevant measures were required for the widespread penetration of the dairy insurance policy in Punjab and more extension services were needed to create awareness about it.